Problematika dalam Implementasi Penilaian Autentik pada Kurikulum 2013 - Putri, Indah Desmi; Adisel, Adisel; Sari, Dwi Permata; Novera, Anes; Albab, Nurhaq (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to find out the problems in the implementation of authentic assessment in the 2013 curriculum at SMPN 7 Bengkulu City. This type of research uses a qualitative descriptive method with a case study approach. In data analysis, the data obtained were then collected and analyzed descriptively. The results of the study illustrate that, generally in the application of authentic assessment teachers are faced with internal and external problems so that authentic assessments carried out by teachers cannot run well. In conclusion, therefore the teacher tries to apply authentic assessment by managing time as well as possible when students learn, with this authentic assessment can run effectively and efficiently as it should. Keywords: Implementation, Curriculum 2013, Authentic Assessment